The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1074/jbc.m000279200
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-scanning Mutagenesis of a Critical Tryptophan in the “Minor Groove Binding Track” of HIV-1 Reverse Transcriptase

Abstract: Biochemical and molecular modeling studies of human immunodeficiency virus type 1 reverse transcriptase (RT) have revealed that a structural element, the minor groove binding track (MGBT), is important for both replication frameshift fidelity and processivity. The MGBT interactions occur in the DNA minor groove from the second through sixth base pair from the primer 3-terminus where the DNA undergoes a structural transition from A-like to B-form DNA. Alanine-scanning mutagenesis had previously demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…In this model the MGBT of the p66 thumb spans approximately positions Ϫ13 through Ϫ16. One proposed role for the MGBT is as a sensor of nucleic acid geometry during translocation (19). The MGBT is very close to the region of the PPT where LNA substitution eliminates hydrolysis at the PPT/U3 junction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this model the MGBT of the p66 thumb spans approximately positions Ϫ13 through Ϫ16. One proposed role for the MGBT is as a sensor of nucleic acid geometry during translocation (19). The MGBT is very close to the region of the PPT where LNA substitution eliminates hydrolysis at the PPT/U3 junction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mutagenesis studies (27) have suggested that this motif functions as a ''sensor'' of duplex configuration, detecting base pair alterations introduced by lesions. Localized destabilization (enhanced melting) of this PPT region could therefore compromise thumb contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Gly 262 , Lys 263 , and Trp 266 of helix ␣H are part of the minor groove binding track, a motif implicated in correct tracking of the enzyme over nucleic acid (29). Mutagenesis studies suggest that this motif could function as a "sensor" of duplex configuration, detecting base pair alterations introduced by lesions (30). Since crystallographic (11) and chemical footprinting data (10) have both identified distortions within the HIV-1 PPT, recognition of this structure by the minor groove binding track is a plausible mechanism that helps position the RNase H catalytic center directly over the PPT-U3 junction.…”
Section: Discussionmentioning
confidence: 99%